Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Pertumbuhan Penjualan, Dan Laba Akuntansi Terhadap Return Saham Pada BUMN Yang Terdaftar Di BEI Tahun 2018-2020 - Agus Wahyudi (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aims to examine the effect of profitability, leverage, company size, sales growth, and accounting profit on stock returns in state-owned companies listed on the Indonesia Stock Exchange with the 2018-2020 observation year. The type of research used is quantitative research with an associative approach. The sampling technique uses purposive sampling so that the number of samples is 16 companies with a total of 48 observations. The results show that profitability and company size have no effect on stock returns. Then leverage and sales growth have a negative effect on stock returns. While accounting profit has a positive effect on stock returns. as much as 46.8% of stock return variables can be explained by the variables of profitability, leverage, company size, sales growth, and accounting profit, the rest is influenced by other variables not included in this study.